A teacher's guide to classroom assessment : - Butler, Susan M. (Jossey-Bass, 2006)
A Teacher’s Guide to Classroom Assessment is a comprehensive guide that shows step-by-step how to effectively integrate assessment into the classroom. Written for both new and seasoned teachers, this important book offers a practical aid for developing assessment skills and strategies, building assessment literacy, and ultimately improving student learning. Based on extensive research, this book is filled with illustrative, down-to-earth examples of how classroom assessment works in classrooms where assessment drives the instruction. The authors present the Classroom Assessment Cycle—Clarifying learning targets, Collecting assessment evidence, Analyzing assessment data, and Modifying instruction based upon assessment data—that demonstrates how one assessment action must flow into the next to be effective. Each chapter details the kinds of assessment evidence that are the most useful for determining student achievement and provides instruction in the analysis of assessment data